2016
DOI: 10.1007/s40746-016-0068-2
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Cost Through Standardization

Abstract: Opinion statementThe drive for standardization of care within pediatrics based on medical evidence is gaining momentum among hospitals and providers. Initiated by care guidelines with origins in specialty societies, adoption of pathways is now being implemented in many settings. The keys to success of these algorithms in narrowing practice variation and their potential contribution to reducing utilization of unnecessary resources are not uniformly addressed in advance. Clinical guidelines are often not updated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…These results demonstrate that there is much room for cost reduction and standardization in support of cost reduction, one of the quadruple aims of healthcare quality improvement [ 51 ]. Reducing large cost variation through standardization can lead to cost savings [ 52 , 53 ]. Our findings may be useful to policymakers for planning and resource allocation decisions.…”
Section: Consclusionsmentioning
confidence: 99%
“…These results demonstrate that there is much room for cost reduction and standardization in support of cost reduction, one of the quadruple aims of healthcare quality improvement [ 51 ]. Reducing large cost variation through standardization can lead to cost savings [ 52 , 53 ]. Our findings may be useful to policymakers for planning and resource allocation decisions.…”
Section: Consclusionsmentioning
confidence: 99%
“… 22 In their study of the effect of standardization on reducing costs for pediatric patients, Friedman and Fulton found that standardized assessment and management plans, similar to CPGs, had the potential to reduce patient care costs in pediatric cardiology by up to 51%, when implemented consistently. 25 …”
Section: The Role Of Standardization In Healthcarementioning
confidence: 99%
“…Without regular appraisal of new or emerging evidence, and the subsequent updating of CPG recommendations, providers may base their decision-making on outdated evidence, which may contribute to poorer outcomes, or in unnecessary healthcare resource utilization. 25 …”
Section: The Role Of Standardization In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…6,7,11,12 In a publicly funded health care system with finite human and financial resources, it is essential to improve the efficiency of care (by optimizing expenditures and concentrating quality of delivery), which requires the ability to determine costs for all infants. 3,6,7,13 Advancements in this area are currently limited by the need of harmonized and reliable costing data in Canada and in other countries. 9 Furthermore, most costing studies have focused on preterm populations, relied on average costs per diagnostic groups or estimated costs using nonstandardized databases.…”
mentioning
confidence: 99%